Synthesis of carbon nanotubes by catalytic chemical vapour deposition: A review on carbon sources, catalysts and substrates - Shah, Khurshed A.; Tali, Bilal A. (Materials science in semiconductor processing, 2016)
Carbon nanotubes (CNTs) have been extensively studied during the past two decades and Catalytic Chemical Vapour Deposition (CCVD) technique has been untiredly employed by researchers to produce CNTs of various crystallographic configurations. In this paper the material aspects carbon sources, catalysts and substrates with regard to CCVD synthesis of carbon nanotubes are reviewed in light of latest developments and understandings in the field. The role of these materials in synthesis of CNTs is explained keeping the upto date literature in view. Latest research reports and their findings are presented with regard to effects of growth control aspects such as temperature, vapour pressure and catalyst concentration on CNT formation. Besides recent understandings with regard to preferential growth of CNTs are also discussed. From this literature review it is found that carbon diffusibility and carbon solubility of any catalyst are two important factors in determining CNT nucleation and growth. Moreover, addition of catalyst species to any transition metal catalyst can improve the catalyst performance and addition of water, air, alcohol etc. during CCVD process can increase the activity and lifetime of the catalyst besides enhances the production of CNTs.